Production and emission test of refined coconut oil ethyl ester biodiesel and ethanolysis of crude jatropha oil - Ferrer, Emmanuel Laurea
This study investigated the production of refined coconut oil ethyl ester biodiesel and well as ethanolysis of crude jatropha oil. It aimed to determine the process conditions for a successful conversion of coconut oil and jatropha oil to ethyl ester biodiesel and to determine whether to product properties conform to Philippine National Standards (PNS) specifications for B100 fatty acid methyl ester biodiesel. This study determined the emission characteristics using a 3.3 kW single-cylinder Sumo diesel engine generator set at varying biodiesel blends and electrical loads with neat automotive diesel oil (ADO) as the base fuel. Preliminary experiments were conducted at different catalyst concentrations and process temperatures. The density, kinematic velocity. Distillation Atmospheric Equivalent Temperature (AET) at 50% and 90% recovery, cetane index, ester content, heating value, acid value, pour point, cloud point, % water content, flash point, total and free glycerine were measured and compared with local standards. Semtech DS emission analyzer was used to study the emission characteristics of the coconut ethyl ester biodiesel at B1, B2 and B5 Blends.